ANALISIS PERGAULAN SOSIAL PADA PESERTA DIDIK KELAS XI SMA NEGERI 01 AMBAWANG - Ilhamdi, Hikmah; Wicaksono, Luhur; Yuline, Yuline (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe method used in this research is descriptive method because it explains about social interaction in class XI students at SMA Negeri 01 Ambawang. The sample of this study was 35 students in class XI of SMA Negeri 1 Ambawang. This study uses indirect communication techniques using a tool in the form of a questionnaire or questionnaire. The questionnaire is addressed to students to find out how much students' understanding of the material that has been delivered and given to students. This research is a quantitative approach because in analyzing the data the descriptive statistical technique is used. The characteristics of positive social relations in class XI students at Ambawang High School 01 reached 85.71% in the